2020
DOI: 10.22270/jddt.v10i4-s.4209
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis And Anagesic activities of Quinazolin-4(3H)-One, 2-Methyl-4(3H)-Quinazolinone and 2–Phenyl-4(3H)-quinazolin-4(3H)–one

Abstract: Background: Objective: The current study is aimed at the synthesis of these quinazolinone derivatives quinazolin-4(3H)-One, 2-Methyl-4(3H)-quinazolinone and 2–Phenyl-4(3H)-quinazolin-4(3H)–one and evaluate them for their analgesic activity. Method: The condensation of 2-amino-methyl-4-methoxybenzoate with acetic anhydride yielded the cyclic compound 2-methyl-4, 5-disubstituted-1, 3-benzo-oxazine-4-one which further produce a novel 2,3-disubstituted quinazolin-4 ones via the reaction with hydrazine hydrate The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…2-(2-Substitutedphenyl)quinazolinones are reported as drug leads or prodrugs for anti-analgesic, antitumor, antiviral, antibacterial, anti-inflammatory, and anticonvulsant activities. [8][9][10][11][12][13] 3-Methyl-quinazolinone derivatives were reported as EGFR inhibitors. [14] Peyressatre et al reported quinazolinone derivatives can inhibit CDK5 activity and glioma cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…2-(2-Substitutedphenyl)quinazolinones are reported as drug leads or prodrugs for anti-analgesic, antitumor, antiviral, antibacterial, anti-inflammatory, and anticonvulsant activities. [8][9][10][11][12][13] 3-Methyl-quinazolinone derivatives were reported as EGFR inhibitors. [14] Peyressatre et al reported quinazolinone derivatives can inhibit CDK5 activity and glioma cell proliferation.…”
Section: Introductionmentioning
confidence: 99%